2008
DOI: 10.1007/s00464-008-0266-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of obesity on short-term results of laparoscopic rectal cancer resection

Abstract: Obesity increases operative duration and conversion rate of rectal laparoscopic resection for cancer. Although obesity is associated with a worse preoperative evaluation, there is no increase in relevant morbidity and no impairment of oncological safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
126
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(133 citation statements)
references
References 23 publications
2
126
2
1
Order By: Relevance
“…There is also burgeoning evidence that laparoscopic colorectal surgery can be safely completed in the obese with conversion rates varying from 7.3-46%. 8,9 Thus, obesity itself should not be used as a reason not to offer laparoscopic surgery. Nonetheless, within the obese group, there are patients who are undoubtedly more challenging.…”
Section: Discussionmentioning
confidence: 99%
“…There is also burgeoning evidence that laparoscopic colorectal surgery can be safely completed in the obese with conversion rates varying from 7.3-46%. 8,9 Thus, obesity itself should not be used as a reason not to offer laparoscopic surgery. Nonetheless, within the obese group, there are patients who are undoubtedly more challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports have demonstrated that obesity is associated with high conversion rates [16][17][18]. One of the difficulties of performing laparoscopic surgery on obese patients is obtaining good visualization of the surgical field.…”
Section: Discussionmentioning
confidence: 99%
“…A French retrospective review of 210 mesorectal excisions, where most patients received neoadjuvant radiotherapy, found no difference in lymph node sampling (P ¼ .23) between obese (BMI >30) and nonobese. 46 Another retrospective analysis that included 254 patients with rectal adenocarcinoma stratified lymph node yield by BMI, with obesity defined by BMI >30. 47 Two thirds of the patients were treated with neoadjuvant radiotherapy and/or chemotherapy, and a minority of patients underwent laparoscopic resection (4% of obese, OBESITY AND COLORECTAL CANCER/GRIBOVSKAJA-RUPP ET AL 11% nonobese).…”
Section: Obesity and Colorectal Surgery Outcomesmentioning
confidence: 99%
“…56 Short-term morbidity for rectal cancer resection seems to be increased with obesity. In addition, obesity is reported to be significantly associated with rates of anastomotic leak, 57,58 parastomal hernia, 59 wound infection, 60,61 length of laparoscopic surgery according to BMI, [46][47][48]60 length of laparoscopic surgery according to visceral adipose area, 62,63 overall and systemic complications, 62 more frequent conversion to laparotomy, 46,64 more blood loss, 47,58,63 and longer hospital stay. 48 In addition, obese patients undergoing laparoscopic colorectal surgery are at an increased risk for conversion to open operation and operative times are significantly increased for obese patients having rectal cancer surgery.…”
Section: Obesity and Colorectal Surgery Outcomesmentioning
confidence: 99%